Indonesia Perancangan Jaringan Komputer untuk Sekolah Dasar Dengan Sistem Manajemen Bandwidth Hierarchical Token Bucket - Simbolon, Jesika Marsaulina; Harafani, Hani; Astuti, Rachmawati Darma (Universitas Bumigora, 2021)
In the development of internet service technology, it has become a major requirement as a means of communication and exchanging information. Especially in the field of education such as elementary schols, internet facilities are very much needed where the users are administrative staff, teachers, students via the internet can access various knowledge needed quickly, so that it can simplify the learning process. Therefore, the bandwidth sharing system or it can be called bandwidth management must be in accordance with the conditions of the network service to be applied and bandwidth management is indispensable for multi-service networks, because the more and more varied applications that can be served by a network have an effect on link usage. In the network. The method in this research uses library research and the implementation uses the Hierarchical Token Bucket method, which is an application that function to regulate the distribution of bandwidth. The purpose of this analysis is to provide a bandwidth management system to make a fair distribution for users connected to the network. The results showed that the Hierarchicak Token Bucket method can regulate bandwidth usage for each client when downloading, uploading, streaming and browsing. Keyword: Bandwidth, HTB, Design, Network, Computer.